Analisis Kemampuan Pemahaman Matematis Mahasiswa dalam Menyelesaikan Soal Integral Tentu Berdasarkan Teori APOS - Handayani, Ita; Widyah Noviana (Universitas Veteran Bangun Nusantara, 2024)
This study aims to describe the mathematical understanding ability of students regarding the concept of definite integral based on APOS Theory, and describe the achievement of each indikator of students' mathematical understanding ability regarding the concept of definite integral of algebraic functions based on APOS Theory. The research method used is descriptive qualitative. The data collection techniques used in this study were written tests and interviews. The results showed that the achievement in question number one on the K indikator 88.89%, L 83.33% and S 69.44%, most of the students who were able to solve the problem meant that they had been able to organise the actions, processes, and objects they had so that based on APOS theory, the student was at the level of understanding the scheme. Achievement in question number two on indikator K 80.55%, L 58.33% and S 50%. Most students are only able to identify properties and conditions, meaning that students only have the ability to understand at the action stage. Achievement in question number two on indikator K 86.11%, L 66.67% and S 63.88%. Most students are only able to identify properties and conditions and work on problems according to the steps.